2004
DOI: 10.1016/s0011-393x(04)90025-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a weight-reduction program with orlistat on serum leptin levels in obese women: A 12-week, randomized, placebo-controlled study

Abstract: Background: Leptin, which has been identified as an antiobesity hormone, regulates body weight by controlling food intake and energy expenditure via the hypothalamic-pituitary-gonadal axis. It appears that leptin may be an important factor in obesity management. Orlistat, a pancreatic lipase inhibitor, could reduce fat absorption and promote weight loss due to leptin metabolism.Objective: The purpose of this study was to investigate the effects of orlistat therapy on serum leptin levels.Methods: Obese women (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Of these 534 publications, 17 were selected for full-text assessment. After careful assessment, 12 articles met the inclusion criteria and were selected for meta-analysis [17,[26][27][28][29][30][31][32][33][34][35][36]. Reasons for rejecting the other five articles were as follows: three were uncontrolled studies, one study was not written in English, and one study [37] reported data for the overall population without providing separate numerical values for leptin levels in the orlistat and placebo groups.…”
Section: Flow Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 534 publications, 17 were selected for full-text assessment. After careful assessment, 12 articles met the inclusion criteria and were selected for meta-analysis [17,[26][27][28][29][30][31][32][33][34][35][36]. Reasons for rejecting the other five articles were as follows: three were uncontrolled studies, one study was not written in English, and one study [37] reported data for the overall population without providing separate numerical values for leptin levels in the orlistat and placebo groups.…”
Section: Flow Of Included Studiesmentioning
confidence: 99%
“…The maximum licensed dose of orlistat (360 mg/day) was used in the included trials, with the exception of one study where the dose administered was not revealed [26]. Duration of studies ranged from 3 months [34][35][36] [17,[28][29][30]] to 36 months [32,33]. All trials were designed as parallel-group studies [17,[26][27][28][29][30][31][32][33][34][35][36], all were double arm parallel-group studies [17,[26][27][28][29][30][31][32][33][34]36], and one was a triple arm parallel-group study [35].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Hsieh et al (25), after one year of treatment in Asian obese patients, observed that over the same range of BMI, body fat% and waist circumference loss, the orlistat treatment group experienced more significant changes in plasma levels of leptin than the control group. On the other hand, Ozcelik et al (26) showed, after 12 weeks, a similar decrease in plasma leptin in 14 patients who received orlistat and 10 patients that received placebo.…”
Section: Discussionmentioning
confidence: 90%
“…The significant effect of ThT on leptin is specially of interest, with regard to the importance of this adipokine in weight regulation (27). Recently proposed antiobesity compounds that act on accumulation of visceral fat have also been observed to influence leptin levels (28), (29), (30).…”
Section: Thioflavin T Counteracts Obesitymentioning
confidence: 99%